2001
DOI: 10.1002/1096-9845(200102)30:2<173::aid-eqe3>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of soil liquefaction from strong motion records

Abstract: During the recent earthquakes in Japan and the U.S.A. a number of records from liqueÿed-soil sites have been obtained. The ground motion parameters from these sites were studied and several methods for detection of liquefaction from seismic records were developed. The methods, however, focus mainly on the horizontal ground motion and may interpret as liquefaction-induced some records from soft-soil deposits or records with dominant surface waves, at which sites the phenomenon was not observed. Besides, not all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…According to previous studies conducted by Kostadinov and Yamazaki (2001) and with the results of our STFT analysis for the observed horizontal ground motions, liquefaction can occur during the mainshocks due to abrupt changes in the predominant frequency. Liquefaction is a process by which sediments below the water table temporarily lose strength gradually and behave as a viscous liquid rather than as a solid, as shown in Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…According to previous studies conducted by Kostadinov and Yamazaki (2001) and with the results of our STFT analysis for the observed horizontal ground motions, liquefaction can occur during the mainshocks due to abrupt changes in the predominant frequency. Liquefaction is a process by which sediments below the water table temporarily lose strength gradually and behave as a viscous liquid rather than as a solid, as shown in Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Ground motion parameters from liquefiedsoil sites have been examined in a number of studies which have employed several methods for assessing liquefaction based on strong motion records. Nakayama et al (1998), Miyajima et al (1998), Ozaki (1999), and Kostadinov and Yamazaki (2001) reported various methods that consider ground motion parameters such as peak horizontal ground acceleration, maximum spectrum intensity, and maximum horizontal ground displacement. The respective method evaluates the occurrence of liquefaction either positively or negatively if these parameters exceed certain limit values.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable changes were observed as the motion propagates from the dense sand layer to the ground surface: more long-period components were present within the loose sand layer and in the ground surface when the main shaking occurred, and the peak amplitude of acceleration decreased. The alteration of acceleration time histories including frequency and amplitude indicates liquefaction in the loose sand layer (40).…”
Section: Soil Responsementioning
confidence: 99%
“…Разжижение почвы представляет собой процесс, в котором в течение очень короткого периода времени (несколько секунд или десятков секунд) при сотрясении грунта, почва трансформируется из своего нормального состояния в состояние тяжелой, жидкой массы [24]. Несколько моделей мониторинга описаны в литературе [25,26,27,28,29] для наземного или космического наблюдения. Одна из них показана на рис.…”
Section: рис 4 пример системыunclassified